Análise comparativa de modelos de maturidade em gerenciamento de projetos: uma contribuição ao estudo da maturidade organizacional em setores de engenharia - Silva, Rafael Rodrigues da (2011)
The purpose of this dissertation is to formulate guidelines for the improvement of maturity models, or the development of new ones, aiming at its application to project departments. The maturity of project management has become critical for organizations that develop projects and want to stand out in the market they serve. For this purpose, maturity models provide paths in order to guarantee that the institutionalization of project management is achieved in the best possible way. Generally, these models assess the organization, define its current situation in managing projects and propose steps to be performed in the search of more advanced levels of maturity. With the objective of contributing to the improvement of maturity models for specific cases, a bibliographical research was conducted for the preparation of a comparative analysis matrix and performed a case study for application of two maturity models (MMGP and PMMM levels 2 and 3), selected based on criteria found in the literature, in an engineering department of an oil company. The case study supported the realization of a comparative analysis of models, from which guidelines were formulated for improvement. The results showed that thedepartment is evaluated in a medium stage of maturity, recording significant progress in some dimensions assessed. They also found that the results of applying the two models are presented as complementary, although the model is highlighted by the greater depth of MMGP diagnostic, considering many variables in their levels of maturity than model PMMM (levels 2 and 3).Finally, directions have been formulated that contribute to the improvement of maturity models, taking in account the organizational environment in which this work was developed